1994
DOI: 10.1007/bf00008502
|View full text |Cite
|
Sign up to set email alerts
|

Four fish species new to the Omo-Turkana basin, with comments on the distribution ofNemacheilus abyssinicus (Cypriniformes: Balitoridae) in Ethiopia

Abstract: Four fish species, Pollimyrus isidori (Mormyridae), Barbus paludinosus, Labeo forskalii (Cyprinidae), and Nemacheilus abyssinicus (Balitoridae), new to the Omo-Turkana basin, were recorded from the Gojeb River, a tributary of the Omo River (south-western Ethiopia) . Occurrence of the latter species in the upper reaches of the Blue Nile and of the Omo drainage substantiates the belonging of the upper parts of these water systems to the Abyssinian highlands ichthyofaunal province . 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
0
9
1
Order By: Relevance
“…Of 37 genera documented in the modern Omo-Turkana Basin (including Lake Turkana; this list was compiled from Boulenger, 1906;Pellegrin, 1935;Hopson and Hopson, 1982;Leveque et al, 1991;Dgebuadze et al, 1994;Golubtsov and Berendzen, 1999), I have identified nine in the Kibish deposits. Catfish are the best represented, with four genera identified in the Kibish deposits and 10 (or nine if Clarias and Heterobranchus are grouped) in the modern fauna.…”
Section: Composition Of the Faunamentioning
confidence: 99%
See 1 more Smart Citation
“…Of 37 genera documented in the modern Omo-Turkana Basin (including Lake Turkana; this list was compiled from Boulenger, 1906;Pellegrin, 1935;Hopson and Hopson, 1982;Leveque et al, 1991;Dgebuadze et al, 1994;Golubtsov and Berendzen, 1999), I have identified nine in the Kibish deposits. Catfish are the best represented, with four genera identified in the Kibish deposits and 10 (or nine if Clarias and Heterobranchus are grouped) in the modern fauna.…”
Section: Composition Of the Faunamentioning
confidence: 99%
“…Although older collections were made (e.g., Boulenger, 1906;1909-1916, the classic work on Omo River fishes was done as part of the ''Mission Scientifique de l'Omo'' (Pellegrin, 1935). The most recent compilation of the modern Omo-Turkana fish fauna is more than ten years old (Leveque et al, 1991), and at least five new species have been discovered in this system since (Dgebuadze et al, 1994;Golubtsov and Berendzen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the latter was synonymized with P. i. osborni and P. osborni was recognized as a distinct species occurring in the Congo basin (Konan, Boden, & Snoeks, ). In addition, a species P. isidori was reported from the Omo‐Turkana basin in southwestern Ethiopia (Dgebuadze, Golubtsov, Mikheev, & Mina, ). Now, this basin is isolated, but there is clear evidence for its repeated connections to the Nile system in the past: The last connection occurred in early Holocene (Johnson & Malala, ).…”
Section: Introductionmentioning
confidence: 99%
“…Enteromius paludinosus (Peters, 1852) Gojeb River (DgeBuaDze et al 1994); previously reported as Barbus paludinosus; present in east, central and southern Africa; 15 cm SL (Skelton 1993).…”
Section: Cypriniformes Cyprinidae (22 Species)mentioning
confidence: 97%
“…Afronemacheilus kaffa Prokofiev & Golubtsov, 2013 Identified as Afronemacheilus abyssinicus (non Boulenger, 1902) from the Gojeb River (DgeBuaDze et al 1994), and later described as Afronemacheilus kaffa Prokofiev & Golubtsov, 2013; endemic to Omo River basin; 5.5. cm SL (prokofieV & goluBtSoV 2013).…”
Section: Nemacheilidae (1 Species)mentioning
confidence: 99%